Avaliação dos parâmetros físico-químicos das blendas de biodiesel metílico e etílico de chichá (Sterculia striata) com diesel mineral - Gabriel, Rafaela (2017)
A study of the physicochemical properties of biodiesel from methyl and ethyl Sterculia striata and its mixtures with mineral diesel was conducted in order to evaluate the quality of biodiesel produced, to analyze the applicability of biodiesel / diesel blends and to predict their properties from models empirical and thermodynamic tests a imingto determinet heir operability in diesel power e dengines. The blends B0, B10, B15, B20, B40, B60, B80 and B100 were analyzed for viscosity, density and clogging point, which are important quality parameters cited in the Resolution of the National Agency of Petroleum, Natural Gas and Biofuels (ANP). The biodiesel and its mixtures with mineral diesel can be used as fuel because they present physico chemical properties similar to diesel oil and provide an acceptable dynamics for the combustion process. The tests were performed over a wide temperature range and at atmospheric pressure. The Sterculia striata was chosen as raw material in this study because it is a source of triglycerides little explored and because they are not directly competitors of the food production, being intercropped with agricultural activities. The kinematic viscosity and specific mass data were modeled from empirical correlations in order to predict the fundamental properties of biodieses and their blends with diesel. The experimental data of the specific mass were also evaluated for the understanding of the thermodynamic behavior through the Peng-Robinson (PR) State Equation based on the concept of parameter estimation by objective function minimization using the critical properties of biodiesel (Tc, Pc, Vc and ω). The critical properties of the biodiesel and its mixtures were determined by the Constantinou and Gani (CG) group contribution method based on the groups of the UNIFAC thermodynamic model. The specific mass estimates were performed in Matlab environment, using the fminsearch routine that was adopted as a minimization tool. The results showed that the studied properties, specific mass, kinematic viscosity and clogging point may be influenced by both the temperature and the variations of the biodiesel fractions in the mixtures. Kinematic viscosity and specific mass decreased with increasing temperature and increased with the percentage increase of biodiesel in the blend. The clogging point also increased with the increase in the biodiesel fraction in the blend. The results of empirical and thermodynamic predictions were satisfactory; the Peng-Robinson equations were adequate for the estimation of the specific mass, being very close to those found experimentally, presenting percentage errors lower than 0.3%.